Penanaman nilai akhlak pada peserta didik dalam pendidikan Islam - Ramadhani, Dwika Ayu (Maliki Interdisciplinary Journal, 2024)
Islamic education must include instilling moral principles in children, especially students. Within the framework of Islamic education, this article emphasizes the value of education and moral values. Religious education is incomplete without moral formation which becomes a solid moral foundation in developing personal character. Honesty, compassion, and integrity are strong moral principles that guide daily life and help students overcome moral difficulties. The moral values that are instilled will be a provision for students in childhood and adulthood, so that the moral teachings that are instilled in students should be based on the Al-Qur'an and Sunnah which are useful in instilling moral ideals. Forming people with noble and responsible morals in accordance with the teachings of the Islamic religion requires a large investment in Islamic education. Good moral education is in line with Islamic teachings today, where moral difficulties are increasingly complex.